Managing the smart revolution in tourism firms innovation and value creation in the era of data - Navarro Meneses, Francisco J. (CAB International, 2023)
"This practical book explains the key ideas that tourism practitioners and decision-makers must know to understand Smart Technologies, and the management principles supporting them. Real-life cases are provided to illustrate the true dimension of the "smart" phenomenon and the new frontiers that are yet to open in the coming years." --